Central Nervous System Demyelination and Remyelination is Independent from Systemic Cholesterol Level in Theiler's Murine Encephalomyelitis. (10th June 2015) - Raddatz, Barbara B.; Sun, Wenhui; Brogden, Graham; Sun, Yanyong; Kammeyer, Patricia; Kalkuhl, Arno; Colbatzky, Florian; Deschl, Ulrich; Naim, Hassan Y.; Baumgärtner, Wolfgang; Ulrich, Reiner
Abstract: High dietary fat and/or cholesterol intake is a risk factor for multiple diseases and has been debated for multiple sclerosis. However, cholesterol biosynthesis is a key pathway during myelination and disturbances are described in demyelinating diseases. To address the possible interaction of dyslipidemia and demyelination, cholesterol biosynthesis gene expression, composition of the body's major lipid repositories and Paigen diet‐induced, systemic hypercholesterolemia were examined in Theiler's murine encephalomyelitis (TME) using histology, immunohistochemistry, serum clinical chemistry, microarrays and high‐performance thin layer chromatography. TME‐virus (TMEV)‐infected mice showed progressive loss of motor performance and demyelinating leukomyelitis. Gene expression associated with cholesterol biosynthesis was overall down‐regulated in the spinal cord of TMEV‐infected animals. Spinal cord levels of galactocerebroside and sphingomyelin were reduced on day 196 post TMEV infection. Paigen diet induced serum hypercholesterolemia and hepatic lipidosis. However, high dietary fat and cholesterol intake led to no significant differences in clinical course, inflammatory response, astrocytosis, and the amount of demyelination and remyelination in the spinal cord of TMEV‐infected animals. The results suggest that down‐regulation of cholesterol biosynthesis is a transcriptional marker for demyelination, quantitative loss of myelin‐specific lipids, but not cholesterol occurs late in chronic demyelination, and serum hypercholesterolemia exhibited no significant effect on TMEV infection.